Utilization of waste as a constituent ingredient for enhancing thermal performance of bricks – a review paper - Raut, Ashwin Narendra; Gomez, Christy Pathrose (Scientific Research Solution, 2016)
In view of the environmental regulations, practitioners have been inclined to use bricks with higher insulation capability, however with minimal attention to sustainable material composition, let alone waste material. From a research perspective, in the wake of the growing concerns for the environment, the use of waste material to develop bricks which can exhibit suitable characteristics attributed to the material composition has been on the rise. However, the extant literature on utilization of waste materials for brick mix design has neglected to provide detailed literature review on the influence of waste materials on the thermal performance of bricks. Methods: This paper provides detailed review of research conducted on thermal properties of bricks produced from various types of waste. Influence of the method of manufacturing and type of waste on thermal performance of bricks is discussed. A sustainability selection criteria format is provided to assist optimal decision making in considering alternative sustainable waste material. Findings: A sustainability selection criteria format is provided to assist optimal decision making in considering alternative sustainable waste material. Applications: The outcome of this paper can serve as a common reference for practitioners and researchers attempting to seek out solutions for further improving overall quality of thermally insulated waste-incorporated bricks, paving the way for more focused research on waste utilization in the development of more sustainable wall material based on the current brick production process.